Along came a spider [videorecording (DVD)] - Tamahori, Lee; Freeman, Morgan; Wincott, Michael, 1959-; Potter, Monica; Patterson, James, 1947- (Paramount, 2017)
Detective Alex Cross and secret service agent Jezzie Flannigan search for a congressman's kidnapped daughter.